How is social support associated with depressive tendencies? the mediating role of self-efficacy - Jun, Wu; Mohd Khir, Azlina; Azeqa Ma'rof, Aini (Human Resources Management Academic Research Society (HRMARS), 2024)
This research aims to examine the relationships between social support, self-efficacy, and depressive tendencies among undergraduate students of two schools in Yunnan Province, China. In total, 468 undergraduates participated in the study, which employed the Perceived Social Support Scale (PSSS), Generalized Self-Efficacy Scales (GSES), and Beck Depression Inventory (BDI). The Pearson correlation analysis was used to investigate the associations between the research variables, while the Bootstrap test was used to examine the mediating effect of self-efficacy between social support and depressive tendencies. The research findings indicate that social support is related to depressive tendencies. Undergraduates who show higher degrees of social support would show low levels of depressive tendencies. In addition, self-efficacy was similarly associated with depressive tendencies. The results also show that self-efficacy mediates the relationship between social support and depressive tendencies. The results of this study expand the existing literature review on depressive tendencies by explaining how social support influences depressive tendencies through the mediation role of self-efficacy.